Positive electrode, method for producing same, and lithium secondary battery
By using positive electrode active materials with different particle sizes and cobalt-coated lithium transition metal oxides in lithium secondary batteries, the problem of irreversible capacity loss of negative electrode materials was solved, achieving excellent resistance characteristics and high-temperature life characteristics, and improving battery capacity and high-temperature storage performance.
Patent Information
- Application Number
- CN202480037263.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-30
- Filing Date
- 2024-12-20
- Publication Date
- 2025-12-30
AI Technical Summary
Existing lithium secondary battery anode materials suffer from high irreversible capacity loss during initial charging and discharging, resulting in poor resistance characteristics and high-temperature lifespan.
The cathode employs first and second positive electrode active materials with different average particle sizes. The average particle size of the first positive electrode active material is larger than that of the second positive electrode active material, and the interface resistance is controlled within a specific range. Lithium transition metal oxides containing different doping elements are used, and a cobalt coating is added to the particle surface to improve resistance characteristics and high-temperature lifetime characteristics.
By optimizing the particle size and composition of the cathode material, the battery's resistance characteristics and high-temperature lifespan characteristics were improved, the generation of lithium byproducts was reduced, and the battery's capacity and high-temperature storage performance were enhanced.
Smart Images

Figure CN121241446A_ABST
Abstract
Description
[0001] Cross-reference to related applications
[0002] This application claims the benefit of Korean Patent Application No. 10-2023-0188990 filed on December 21, 2023, and Korean Patent Application No. 10-2024-0151560 filed on October 30, 2024, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0003] This invention relates to a positive electrode, a method for manufacturing the same, and a lithium secondary battery; more specifically, it relates to a positive electrode having improved capacity, resistance characteristics, and high-temperature life characteristics, a method for manufacturing the same, and a lithium secondary battery. Background Technology
[0004] In recent years, with the rapid proliferation of battery-powered electronic devices such as mobile phones, laptops, desktop computers, and electric vehicles, the demand for small, lightweight, and relatively high-capacity rechargeable batteries has increased rapidly. In particular, lithium-ion batteries have attracted significant attention as a power source for mobile devices due to their light weight and high energy density. Therefore, much research and development is underway to improve the performance of lithium-ion batteries. Summary of the Invention
[0005] Technical issues
[0006] The present invention provides a positive electrode, a method for manufacturing the same, and a lithium secondary battery. The positive electrode uses a low-efficiency positive electrode material that can solve the problem of high irreversible capacity loss of negative electrode materials during initial charging and discharging, thereby achieving excellent resistance characteristics, high-temperature life characteristics, and excellent capacity characteristics.
[0007] Technical solution
[0008] [1] The present invention provides a positive electrode, comprising: a positive electrode active material layer, wherein the positive electrode active material layer comprises a first positive electrode active material and a second positive electrode active material having different average particle sizes, wherein the average particle size D of the first positive electrode active material is... 50 The average particle size D of the second positive electrode active material is greater than that of the second positive electrode active material. 50 The first positive electrode active material and the second positive electrode active material comprise single-particle particles, and the interface resistance of the positive electrode with a SOC of 50% measured in a coin half-cell manufactured using the positive electrode is 6.5 Ω to 8.5 Ω, and the interface resistance of the positive electrode with a SOC of 10% measured in a coin half-cell manufactured using the positive electrode is 15 Ω to 19 Ω.
[0009] [2]The present invention provides a positive electrode according to [1], wherein the first positive electrode active material comprises a first lithium transition metal oxide represented by Formula 1:
[0010] (Formula 1)
[0011] Li 1+a1 Ni x1 Co y1 Mn z1 Al w1 M 1 v1 O2
[0012] In Formula 1, a1, x1, y1, z1, w1, and v1 respectively satisfy 0 ≤ a1 ≤ 0.3, 0.82 ≤ x1 < 1.0, 0 < y1 ≤ 0.2, 0 < z1 ≤ 0.2, 0 < w1 ≤ 0.2, 0 ≤ v1 ≤ 0.1, and M 1 is at least one doping element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo.
[0013] [3]The present invention provides a positive electrode according to [1] or [2], wherein the second positive electrode active material comprises a second lithium transition metal oxide represented by Formula 2:
[0014] (Formula 2)
[0015] Li 1+a2 Ni x2 Co y2 Mn z2 Al w2 M 2 v2 O2
[0016] In Formula 2, a2, x2, y2, z2, w2, and v2 respectively satisfy 0 ≤ a2 ≤ 0.3, 0.82 ≤ x2 < 1.0, 0 < y2 ≤ 0.2, 0 < z2 ≤ 0.2, 0 < w2 ≤ 0.2, 0 ≤ v2 ≤ 0.1, and M 2 is at least one doping element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo.
[0017] [4]The present invention provides a positive electrode according to at least one of [1] to [3], wherein the average particle size D 50 of the first positive electrode active material is 6 μm to 12 μm.
[0018] [5] The present invention provides a positive electrode according to at least one of [1] to [4], wherein the average particle size D of the second positive electrode active material is... 50 The thickness ranges from 1.5 μm to 5 μm.
[0019] [6] The present invention provides a positive electrode according to at least one of [1] to [5], wherein the first positive electrode active material comprises a first lithium transition metal oxide and a first coating on the surface of the first lithium transition metal oxide particles and contains 1.5 mol% to 5 mol% cobalt (Co).
[0020] [7] The present invention provides a positive electrode according to at least one of [1] to [6], wherein the second positive electrode active material comprises a second lithium transition metal oxide and a second coating on the surface of the second lithium transition metal oxide particles and contains 0.2 mol% to 2.5 mol% cobalt (Co).
[0021] [8] The present invention provides a positive electrode according to at least one of [1] to [7], wherein the first positive electrode active material and the second positive electrode active material are contained in a weight ratio of 80:20 to 40:60.
[0022] [9] The present invention provides a positive electrode, comprising: a positive electrode active material layer, wherein the positive electrode active material layer comprises a first positive electrode active material and a second positive electrode active material with different average particle sizes, wherein the average particle size D of the first positive electrode active material is... 50 The average particle size D of the second positive electrode active material is greater than that of the second positive electrode active material. 50 The first positive electrode active material and the second positive electrode active material comprise single-particle particles, and have an IRR value of 96 to 166 as defined in Equation 1.
[0023] (Equation 1)
[0024] IRR = R CT50 ×R CT10
[0025] In equation 1, R CT50 R is a dimensionless interfacial resistance (in Ω) of the positive electrode at a SOC of 50% in a coin cell manufactured using the aforementioned positive electrode, and R CT10 It is a dimensionless number of the interfacial resistance (in Ω) of the positive electrode at a SOC of 10% in a coin half-cell manufactured using the positive electrode.
[0026]
[10] The present invention provides a lithium secondary battery comprising: an electrode assembly including a positive electrode and a negative electrode according to any one of [1] to [9]; an electrolyte; and a battery casing containing the electrode assembly and the electrolyte, wherein the negative electrode comprises a silicon-based negative electrode active material.
[0027]
[11] The present invention provides a lithium secondary battery according to
[10] , wherein the negative electrode further comprises a carbon-based negative electrode active material and comprises the silicon-based negative electrode active material and the carbon-based negative electrode active material in a weight ratio of 1:99 to 30:70.
[0028]
[12] The present invention provides a method for manufacturing a positive electrode, the method comprising: (S1) mixing a first positive electrode active material in distilled water for a first rinse, followed by drying; (S2) mixing a second positive electrode active material in distilled water for a second rinse, followed by drying; and (S3) forming a positive electrode active material layer comprising the first positive electrode active material and the second positive electrode active material, wherein the first rinse is performed at a higher temperature than the second rinse, and the average particle size D of the first positive electrode active material is... 50 The average particle size D of the second positive electrode active material is greater than that of the second positive electrode active material. 50 The first positive electrode active material and the second positive electrode active material comprise single-particle particles, and the interface resistance of the positive electrode with a SOC of 50% measured in a coin half-cell manufactured using the positive electrode is 6.5 Ω to 8.5 Ω, and the interface resistance of the positive electrode with a SOC of 10% measured in a coin half-cell manufactured using the positive electrode is 15 Ω to 19 Ω.
[0029]
[13] The present invention provides the method according to
[12] , wherein the first rinsing is performed at 20°C to 40°C.
[0030]
[14] The present invention provides the method according to
[12] or
[13] , wherein the second rinsing is performed at 3°C to 18°C.
[0031]
[15] The present invention provides a method according to at least one of
[12] to
[14] , wherein the first rinsing is performed by mixing the first positive electrode active material at a content of 50% to 70% by weight based on the total weight of distilled water.
[0032]
[16] The present invention provides a method according to at least one of
[12] to
[15] , wherein the second rinsing is performed by mixing the second positive electrode active material at a content of 65% to 85% by weight based on the total weight of distilled water.
[0033]
[17] The present invention provides the method according to at least one of
[12] to
[16] , wherein the first positive electrode active material includes a first lithium transition metal oxide represented by Formula 1:
[0034] (Formula 1)
[0035] Li 1+a1 Ni x1 Co y1 Mn z1 Al w1 M 1 v1 O2
[0036] In Formula 1, a1, x1, y1, z1, w1, and v1 respectively satisfy 0 ≤ a1 ≤ 0.3, 0.82 ≤ x1 < 1.0, 0 < y1 ≤ 0.2, 0 < z1 ≤ 0.2, 0 < w1 ≤ 0.2, 0 ≤ v1 ≤ 0.1, and M 1 is at least one doping element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo.
[0037]
[18] The present invention provides the method according to at least one of
[12] to
[17] , wherein the second positive electrode active material includes a second lithium transition metal oxide represented by Formula 2:
[0038] (Formula 2)
[0039] Li 1+a2 Ni x2 Co y2 Mn z2 Al w2 M 2 v2 O2
[0040] In Formula 2, a2, x2, y2, z2, w2, and v2 respectively satisfy 0 ≤ a2 ≤ 0.3, 0.82 ≤ x2 < 1.0, 0 < y2 ≤ 0.2, 0 < z2 ≤ 0.2, 0 < w2 ≤ 0.2, 0 ≤ v2 ≤ 0.1, and M 2 is at least one doping element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo.
[0041]
[19] The present invention provides a method according to at least one of
[12] to
[16] , wherein the first positive electrode active material comprises a first lithium transition metal oxide and a first coating containing cobalt (Co) on the surface of the first lithium transition metal oxide particles, and the second positive electrode active material comprises a second lithium transition metal oxide and a second coating containing cobalt (Co) on the surface of the second lithium transition metal oxide particles, wherein the cobalt (Co) content in the first coating is greater than the cobalt (Co) content in the second coating.
[0042]
[20] The present invention provides the method according to
[19] , wherein the amount of cobalt (Co) in the first coating is from 1.5 mol% to 5 mol%, and the amount of cobalt (Co) in the second coating is from 0.2 mol% to 2.5 mol%.
[0043] Beneficial effects
[0044] According to the present invention, since it contains a bimodal positive electrode active material and the interface resistance of the positive electrode meets a specific range, the disadvantage of irreversible capacity loss of the negative electrode can be compensated without sacrificing any separate positive electrode material, thereby providing excellent capacity and lifetime characteristics and improving resistance characteristics. Furthermore, the positive electrode of the present invention can reduce gas generation caused by lithium byproducts during high-temperature storage; therefore, lithium secondary batteries including the positive electrode of the present invention can have excellent high-temperature lifetime characteristics. Attached Figure Description
[0045] The accompanying drawings illustrate embodiments of the invention and are intended to further explain the technical concept of the invention in conjunction with the detailed description of this disclosure that follows. Therefore, the invention should not be construed as limited to what is shown in the drawings.
[0046] Figure 1 This is a flowchart of a method for manufacturing a positive electrode active material according to one embodiment of the present invention. Detailed Implementation
[0047] The invention will be described in more detail below.
[0048] The words and terms used in the detailed description and claims herein should not be construed as limited to their usual or dictionary meanings, but should be interpreted as having meanings and concepts corresponding to the technical ideas of the invention, provided that the inventors can appropriately define terms and concepts for the purpose of best describing the invention.
[0049] The terminology used herein is for descriptive purposes only and is not intended to limit the invention. Unless the context clearly indicates otherwise, singular expressions include plural expressions.
[0050] As used herein, it should be understood that the terms “comprising,” “including,” and “having” are intended to specify the presence of a feature, number, step, component, or combination thereof, but do not preclude the possibility of the presence or addition of one or more other features, numbers, steps, components, or combinations thereof.
[0051] As used herein, the term "monoparticle-type particle" refers to a particle composed of fewer than 30 sub-particles. Each "sub-particle" unit that makes up a monoparticle-type particle is called a "nodule". Monoparticle-type particles include "monoparticles" formed from a single nodule and "quasi-monoparticles" as complexes formed from 2 to 30 nodules.
[0052] As used herein, the term “nodule” refers to the sub-particle unit that constitutes a single particle and a quasi-single particle, wherein a nodule can be a single crystal without any crystal boundaries, or a polycrystalline material without grain boundaries when observed with a scanning electron microscope (SEM) at a field of view of 5,000 to 20,000 times magnification.
[0053] As used herein, the term "secondary particle" refers to a particle composed of more than 30 sub-particles. To distinguish it from the sub-particles that constitute a single-particle type particle, each sub-particle unit that constitutes a secondary particle is referred to as a "primary particle".
[0054] In this invention, the term "particle" may include any or all of the following: single particle, quasi-single particle, primary particle, nodule, and secondary particle.
[0055] In this invention, the term "average particle size D" is used. 50 "" refers to the particle size representing 50% of the volumetric cumulative particle size distribution of the positive electrode active material powder, and can be measured using laser diffraction. For example, the average particle size D 50 The measurement can be performed by dispersing the positive electrode active material powder in a dispersant, introducing the dispersion into a commercially available laser diffraction particle size analyzer (e.g., Microtrac MT 3000), irradiating the dispersion with ultrasound at approximately 28 kHz at a power of 60 W to obtain a volumetric particle size distribution map, and then finding the particle size corresponding to 50% of the volumetric accumulation.
[0056] In this invention, the term "interface resistance of the positive electrode at a state of charge (SOC) of 50% or 10%" refers to the resistance measured at the interface between the positive electrode current collector and the positive electrode active material layer in the positive electrode at a SOC of 50% or 10%. Specifically, in this invention, for each coin half-cell manufactured by inserting a separator between the positive electrode and the lithium metal counter electrode of this invention and injecting an electrolyte, and subsequently subjected to two cycles and then charged to SOC 50% or SOC 10%, the "interface resistance of the positive electrode at a SOC of 50% or 10%" can be measured using a Biologic VMP3 device (in the range of 100 kHz to 10 mHz at 25°C), wherein each cycle includes charging at 25°C under constant current (CC) / constant voltage (CV), 0.1 C, 4.2 V, 0.05 C cutoff conditions and discharging at CC, 0.1 C, 3.0 V.
[0057] Carbon-based materials, such as graphite, are primarily used as anode materials in lithium-ion batteries. However, the low capacity per unit mass of carbon-based materials makes it difficult to achieve high-capacity lithium-ion batteries. Therefore, non-carbon-based anode materials that form intermetallic compounds with lithium, such as silicon, tin, and their oxides, are being developed and used as non-carbon-based anode materials that exhibit higher capacity compared to carbon-based materials. However, these anode materials suffer severe irreversible capacity loss during the initial charge / discharge period.
[0058] In this context, methods have been studied and proposed to compensate for the irreversible capacity loss of the negative electrode by using a material that can be used as a lithium-ion supply source or storage device and becomes electrochemically active after the first cycle without reducing the performance of the battery itself as the positive electrode material. For example, there is a method that uses lithium nickel-based oxides (e.g., Li2NiO2) as a sacrificial positive electrode material or an over-discharge inhibitor in the positive electrode.
[0059] However, most lithium nickel-based oxides are expensive and produce significant amounts of lithium byproducts, thus increasing gas production. Therefore, an alternative method is needed.
[0060] To overcome these problems, according to one embodiment, the present invention provides a cathode with excellent resistance characteristics, high-temperature lifetime characteristics, and improved capacity characteristics by introducing a low-efficiency cathode material, a method for manufacturing the cathode, and a lithium secondary battery.
[0061] To develop high-capacity battery cells, silicon-based anode materials with high capacity can be used. However, silicon-based anode materials have low charging and discharging efficiency, resulting in high lithium-ion loss rates due to irreversible reactions. Therefore, with repeated charging and discharging, lithium loss in the cathode active material increases, which can rapidly reduce battery capacity during charging / discharging and lead to the collapse of the cathode active material structure.
[0062] To address this issue, when using a positive electrode active material that is a single-particle type, it is possible to achieve a low-efficiency positive electrode active material that can provide lithium to the silicon-based negative electrode active material during the initial charging and discharging phases. Therefore, even if an irreversible phenomenon occurs where lithium ions desorbed from the positive electrode active material insert into the negative electrode active material and then fail to desorb, the degradation of battery life characteristics can be suppressed or prevented.
[0063] However, when using single-particle positive electrode active materials, compared with using secondary-particle lithium nickel oxide, there is a problem that the lithium diffusion path becomes longer, thereby reducing the mobility of lithium ions and thus reducing resistance and capacity characteristics.
[0064] Therefore, the inventors of this invention provide a positive electrode that exhibits excellent lifetime characteristics by preventing or suppressing lithium-ion loss caused by irreversible reactions of silicon-based negative electrode active materials, thereby preventing or suppressing the degradation of battery resistance characteristics and possessing high energy density. Specifically, this invention provides a positive electrode, a lithium secondary battery containing the same, and a method for manufacturing the same. By using a single-particle type positive electrode active material with a bimodal particle size distribution and by using a positive electrode whose interface resistance is controlled within a specific range, the battery resistance characteristics can be improved, while simultaneously exhibiting excellent lifetime characteristics. Furthermore, this invention provides a positive electrode, a lithium secondary battery containing the same, and a method for manufacturing the same. Since it does not contain a separate excess lithium material like conventional sacrificial positive electrode materials, it exhibits excellent high-temperature lifetime characteristics by minimizing gas generation due to lithium byproducts during storage at high temperatures, and also exhibits excellent capacity characteristics by achieving high energy density.
[0065] The invention will be described in more detail below.
[0066] The positive electrode, the method for manufacturing the positive electrode, and the lithium secondary battery of the present invention include at least one of the following disclosed configurations, and may include any combination of the following technically possible configurations.
[0067] positive electrode
[0068] The positive electrode of the present invention includes a positive electrode active material layer, the positive electrode active material layer comprising particles with different average particle sizes D 50 The first positive electrode active material and the second positive electrode active material. The average particle size D of the first positive electrode active material. 50 The average particle size D of the second positive electrode active material is greater than that of the second positive electrode active material. 50Furthermore, both the first and second positive electrode active materials comprise single-particle type particles. The interface resistance of the positive electrode with a SOC of 50% measured in a coin cell manufactured using the aforementioned positive electrode is 6.5 Ω to 8.5 Ω, and the interface resistance of the positive electrode with a SOC of 10% measured in a coin cell manufactured using the aforementioned positive electrode is 15 Ω to 19 Ω.
[0069] The positive electrode includes a positive electrode active material layer. Specifically, the positive electrode may include a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector.
[0070] As a positive electrode current collector, various positive electrode current collectors used in related technical fields can be used. Examples of positive electrode current collectors include stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, or silver. Positive electrode current collectors can typically have a thickness of about 3 μm to 500 μm, and fine irregularities can be formed on the surface of the positive electrode current collector to enhance the bonding strength of the positive electrode active material. Positive electrode current collectors can be used in various forms, such as membranes, sheets, foils, meshes, porous bodies, foams, or nonwoven fabrics.
[0071] The positive electrode active material layer can be located on the positive electrode current collector, on one side of the positive electrode current collector, or on both sides of it. The positive electrode active material layer can be a single layer or a multilayer structure with two or more layers.
[0072] The positive electrode active material layer includes a first positive electrode active material and a second positive electrode active material.
[0073] The first and second positive electrode active materials have different average particle sizes D. 50 Specifically, the average particle size D of the first positive electrode active material 50 The average particle size D of the second positive electrode active material is greater than that of the second positive electrode active material. 50 Therefore, when the electrode is rolled, the relatively smaller particle size of the second positive electrode active material is filled into the pores of the relatively larger particle size of the first positive electrode active material, thereby increasing the electrode density and achieving high energy density, which enables high capacity characteristics.
[0074] The first positive electrode active material comprises single-particle particles. When the first positive electrode active material comprises single-particle particles, the larger particle size results in a longer lithium diffusion distance, which increases diffusion resistance and may lead to lower positive electrode efficiency. This can be balanced with the application of silicon-based negative electrode active materials. Therefore, the problem of lithium-ion loss due to irreversible capacity when using conventional silicon-based negative electrode active materials can be solved, and lithium deposition on the negative electrode surface can be prevented, thus improving the lifespan characteristics of lithium secondary batteries using the positive electrode of this invention. Furthermore, when using a single-particle first positive electrode active material, unlike when using conventional sacrificial positive electrode materials, the formation of lithium byproducts caused by the sacrificial positive electrode material during charging and discharging can be prevented or suppressed. Therefore, the high-temperature storage characteristics and high-temperature lifespan characteristics are superior to those when using conventional sacrificial positive electrode materials.
[0075] The first positive electrode active material may include a first lithium transition metal oxide containing nickel (Ni), cobalt (Co), manganese (Mn), and aluminum (Al). Unlike ternary lithium transition metal oxides containing nickel, cobalt, and manganese, the first positive electrode active material of the present invention can be structurally stabilized by further including aluminum, which has a strong binding strength with oxygen atoms. Therefore, it can be electrochemically stable at high potentials by suppressing cation mixing during charging and discharging, thereby further improving thermal stability and capacity characteristics.
[0076] Additionally, the first positive electrode active material may include a first lithium transition metal oxide containing at least 82 mol% nickel in all metals other than lithium. In this case, high capacity characteristics of the lithium secondary battery can be achieved.
[0077] Specifically, the first positive electrode active material may include a first lithium transition metal oxide represented by Formula 1:
[0078] (Equation 1)
[0079] Li 1+a1 Ni x1 Co y1 Mn z1 Al w1 M 1 v1 O2
[0080] In Equation 1, M 1 It can be at least one doping element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo. Preferably, M 1It may be at least one doping element selected from the group consisting of W, Y, Ba, Ca, Ti, Mg, Ta, and Nb.
[0081] "1 + a1" may refer to the molar ratio of lithium (Li) in the first lithium transition metal oxide, and it may be 0 ≤ a1 ≤ 0.3, or 0 ≤ a1 ≤ 0.2, or 0 ≤ a1 ≤ 0.15, or 0 ≤ a1 ≤ 0.1. When the above ranges are satisfied, a balance can be achieved between the significant effect of improving the capacity characteristics of the first positive electrode active material according to the controlled Li content and the sinterability during the manufacture of the first positive electrode active material.
[0082] "x1" may refer to the molar ratio of nickel in all metals other than lithium in the first lithium transition metal oxide, and it may be 0.82 ≤ x1 < 1, 0.85 ≤ x1 < 1, 0.90 ≤ x1 < 1, or 0.92 ≤ x1 < 1. When the above ranges are satisfied, a sufficient nickel content in the lithium transition metal oxide that contributes to charging / discharging is ensured, thereby promoting high capacity.
[0083] "y1" may refer to the molar ratio of cobalt in all metals other than lithium in the first lithium transition metal oxide, and it may be 0 < y1 ≤ 0.2, 0 < y1 ≤ 0.18, 0.01 ≤ y1 ≤ 0.15, 0.03 ≤ y1 ≤ 0.12, or 0.05 ≤ y1 ≤ 0.10. When the above ranges are satisfied, by including a small amount of cobalt, good resistance characteristics and output characteristics can be achieved while having a cost advantage.
[0084] "z1" may refer to the molar ratio of Mn in all metals other than lithium in the first lithium transition metal oxide, and it may be 0 < z1 ≤ 0.2, 0 < z1 ≤ 0.18, 0.01 ≤ z1 ≤ 0.15, or 0.03 ≤ z1 ≤ 0.10. When the above ranges are satisfied, the structural stability of the lithium transition metal oxide can be improved.
[0085] "w1" may refer to the molar ratio of Al in all metals other than lithium in the first lithium transition metal oxide, and it may be 0 < w1 ≤ 0.2, 0 < w1 ≤ 0.18, 0.01 ≤ w1 ≤ 0.15, or 0.03 ≤ w1 ≤ 0.10. When the above ranges are satisfied, due to the high binding strength with oxygen, the thermal stability of the lithium transition metal oxide can be improved.
[0086] "v1" may refer to the molar ratio of M in all metals other than lithium in the first lithium transition metal oxide 1 and it may be 0 ≤ v1 ≤ 0.1, 0 ≤ v1 ≤ 0.08, or 0 ≤ v1 ≤ 0.05.
[0087] The first positive electrode active material may include a first lithium transition metal oxide and a first coating on the surface of the first lithium transition metal oxide particles, and the first coating may contain cobalt (Co). The first coating blocks the contact between the lithium transition metal oxide and the electrolyte, thereby suppressing the occurrence of electrolyte side reactions and inhibiting the surface structure degradation of the lithium transition metal oxide that may occur during charging and discharging, thus improving high-temperature lifetime and suppressing the increase in resistance.
[0088] The first coating may contain 1.5 mol% to 5 mol%, 2 mol% to 4.5 mol%, 2.3 mol% to 4 mol%, 2.5 mol% to 3.5 mol%, or 2.7 mol% to 3.3 mol% of cobalt (Co). When the first coating contains cobalt within the above range, by containing a larger amount of cobalt than the second coating (described later) contained in the second positive electrode active material, the positive electrode interface resistance of the coin half-cell including the positive electrode of the present invention at SOC 50% can be reduced, thereby preventing the problem of increased initial resistance during charging and discharging due to reduced ion mobility when using a positive electrode active material as a single particle, thus improving the battery's life characteristics and high-temperature life characteristics.
[0089] The first coating may be formed wholly or partially on the entire surface of the first lithium transition metal oxide particles. Specifically, when the first coating is partially formed on the surface of the first lithium transition metal oxide particles, it may be formed on an area of 5% or more and less than 100%, preferably 20% or more and less than 100% of the total surface area of the first lithium transition metal oxide particles.
[0090] The average particle size D of the first positive electrode active material 50The particle size can be from 6 μm to 12 μm. Specifically, the average particle size of the first positive electrode active material can be greater than 6 μm, greater than 6.2 μm, greater than 6.4 μm, greater than 6.6 μm, greater than 6.8 μm, greater than 7 μm, greater than 7.2 μm, greater than 7.4 μm, greater than 7.6 μm, greater than 7.8 μm, greater than 8 μm, greater than 8.2 μm, or greater than 8.4 μm, and can be less than 12 μm, less than 11.8 μm, less than 11.6 μm, less than 11.4 μm, less than 11.2 μm, less than 11 μm, less than 10.8 μm, less than 10.6 μm, less than 10.4 μm, less than 10.2 μm, less than 10 μm, less than 9.8 μm, less than 9.6 μm, less than 9.4 μm, less than 9.2 μm, less than 9 μm, less than 8.8 μm, or less than 8.6 μm. For example, the average particle size of the first positive electrode active material can be 6 μm to 12 μm, 7.4 μm to 11 μm, 8 μm to 9.6 μm, or 8.2 μm to 9 μm. When the above ranges are met, the rolling density of the positive electrode material can be increased, thus increasing the electrode density during electrode manufacturing and achieving excellent energy density.
[0091] Based on the total weight of the positive electrode active material layer, the content of the first positive electrode active material can be from 20% to 80% by weight, preferably from 30% to 70% by weight, and more preferably from 40% to 60% by weight. When the above range is met, the rolling density can be increased, thereby achieving a high energy density.
[0092] Meanwhile, the second positive electrode active material includes single-particle type particles. When the second positive electrode active material includes single-particle type particles, the larger particle size results in a longer lithium diffusion distance, which increases diffusion resistance. Therefore, the efficiency of the positive electrode may be lower. This allows for efficiency balance with the negative electrode when using silicon-based negative electrode active materials. Thus, the problem of lithium-ion loss due to irreversible capacity when using conventional silicon-based negative electrode active materials can be solved, and lithium deposition on the negative electrode surface can be prevented, thereby improving the lifespan characteristics of lithium secondary batteries using the positive electrode of this invention. Furthermore, when using a second positive electrode active material with single-particle type particles, unlike when using conventional sacrificial positive electrode materials, the generation of lithium byproducts caused by the sacrificial positive electrode material during charging and discharging can be prevented or suppressed. Therefore, the high-temperature storage characteristics and high-temperature lifespan characteristics are superior to those when using conventional sacrificial positive electrode materials.
[0093] The second positive electrode active material may include a second lithium transition metal oxide containing nickel (Ni), cobalt (Co), manganese (Mn), and aluminum (Al). Unlike ternary lithium transition metal oxides containing nickel, cobalt, and manganese, the first positive electrode active material of the present invention can be structurally stabilized by further including aluminum, which has a strong binding strength with oxygen atoms. Therefore, it can be electrochemically stable at high potentials by suppressing cation mixing during charging and discharging, thereby further improving thermal stability and capacity characteristics.
[0094] Additionally, the second positive electrode active material may include a second lithium transition metal oxide containing at least 82 mol% nickel in all metals other than lithium. In this case, high capacity characteristics of the lithium secondary battery can be achieved.
[0095] Specifically, the second positive electrode active material may include a second lithium transition metal oxide represented by Formula 2:
[0096] (Equation 2)
[0097] Li 1+a2 Ni x2 Co y2 Mn z2 Al w2 M 2 v2 O2
[0098] In Equation 2, M 2 It can be at least one doping element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo. For example, M 2 It can be at least one doping element selected from the group consisting of W, Y, Ba, Ca, Ti, Mg, Ta and Nb.
[0099] "1+a2" can refer to the molar ratio of lithium (Li) in the second lithium transition metal oxide, and can be 0≤a2≤0.3, 0≤a2≤0.2, 0≤a2≤0.15, or 0≤a2≤0.1. When the above range is met, a balance can be achieved between the significant effect of improving the capacity characteristics of the second cathode active material by controlling the Li content and the sinterability during the manufacturing of the first cathode active material.
[0100] "x2" can refer to the molar ratio of nickel in all metals other than lithium in the second lithium transition metal oxide, and can be 0.82≤x2<1, 0.85≤x2<1, 0.90≤x2<1, or 0.92≤x2<1. When the above range is met, it ensures that the lithium transition metal oxide has a sufficient nickel content to facilitate charging / discharging, thereby promoting high capacity.
[0101] “y2” may refer to the molar ratio of cobalt among all metals other than lithium in the second lithium transition metal oxide, and may be 0 < y2 ≤ 0.2, 0 < y2 ≤ 0.18, 0.01 ≤ y2 ≤ 0.15, 0.03 ≤ y2 ≤ 0.12, or 0.05 ≤ y2 ≤ 0.10. When the above ranges are satisfied, by including a small amount of cobalt, good resistance characteristics and output characteristics can be achieved while having a cost advantage.
[0102] “z2” may refer to the molar ratio of Mn among all metals other than lithium in the second lithium transition metal oxide, and may be 0 < z2 ≤ 0.2, 0 < z2 ≤ 0.18, 0.01 ≤ z2 ≤ 0.15, or 0.03 ≤ z2 ≤ 0.10. When the above ranges are satisfied, the structural stability of the lithium transition metal oxide can be improved.
[0103] “w2” may refer to the molar ratio of Al among all metals other than lithium in the second lithium transition metal oxide, and may be 0 < w2 ≤ 0.2, 0 < w2 ≤ 0.18, 0.01 ≤ w2 ≤ 0.15, or 0.03 ≤ w2 ≤ 0.10. When the above ranges are satisfied, due to the high binding strength with oxygen, the thermal stability of the lithium transition metal oxide can be ensured.
[0104] “v2” may refer to the molar ratio of M 2 among all metals other than lithium in the second lithium transition metal oxide, and may be 0 ≤ v2 ≤ 0.1, 0 ≤ v2 ≤ 0.08, or 0 ≤ v2 ≤ 0.05.
[0105] The second positive electrode active material may include a second lithium transition metal oxide and a second coating on the surface of the second lithium transition metal oxide particles, and the second coating may contain cobalt (Co). Through the second coating, the contact between the lithium transition metal oxide and the electrolyte is blocked, thereby suppressing the occurrence of electrolyte side reactions, thereby suppressing the deterioration of the surface structure of the lithium transition metal oxide that may occur during charging and discharging, and thus suppressing the increase in resistance and improving the high-temperature life. [[ID=第十七条]]
[0106] The amount of cobalt (Co) contained in the first coating may be greater than the amount of cobalt (Co) contained in the second coating. In this case, the positive electrode interface resistance of the coin half cell including the positive electrode of the present invention at SOC 50% can be reduced, thereby preventing or suppressing the increase in the initial resistance during charging and discharging due to the reduction of ion mobility when using the positive electrode active material as a single particle type particle, thereby improving the life characteristics and high-temperature life characteristics of the battery, and improving the energy density.
[0107] The second coating may contain 0.2 mol% to 2.5 mol%, 0.3 mol% to 2 mol%, 0.5 mol% to 1.5 mol%, or 0.7 mol% to 1.3 mol% of cobalt (Co). When the second coating contains cobalt within the above range, by containing less cobalt than the first coating contained in the first positive electrode active material, the positive electrode interface resistance of the coin half-cell including the positive electrode of the present invention at SOC 50% can be reduced. This prevents or suppresses the problem of increased initial resistance during charging and discharging due to reduced ion mobility when using a positive electrode active material as a single particle, thus improving the battery's life characteristics and high-temperature life characteristics, and improving energy density.
[0108] The second coating may be formed wholly or partially on the entire surface of the second lithium transition metal oxide particles. Specifically, when the second coating is partially formed on the surface of the second lithium transition metal oxide particles, it may be formed on an area of more than 5% and less than 100% or more than 20% and less than 100% of the total surface area of the second lithium transition metal oxide particles.
[0109] The average particle size D of the second positive electrode active material 50 The average particle size can be from 1.5 μm to 5 μm. Specifically, the average particle size of the second positive electrode active material can be 1.5 μm or more, 1.7 μm or more, 1.9 μm or more, 2 μm or more, 2.2 μm or more, 2.4 μm or more, 2.6 μm or more, 2.8 μm or more, or 3 μm or more, and can be less than 5 μm, less than 4.8 μm, less than 4.6 μm, less than 4.4 μm, less than 4.2 μm, less than 4 μm, less than 3.8 μm, less than 3.6 μm, less than 3.4 μm, or less than 3.2 μm. For example, the average particle size of the second positive electrode active material can be 1.5 μm to 5 μm, 2 μm to 4.5 μm, or 2.6 μm to 4.2 μm, 3 μm to 4 μm, or 3 μm to 3.4 μm. When the above range is met, the rolling density of the cathode material can be increased, thus increasing the electrode density during electrode manufacturing and achieving excellent energy density.
[0110] Based on the total weight of the positive electrode active material layer, the content of the second positive electrode active material can be 20% to 80% by weight, 30% to 70% by weight, or 40% to 60% by weight. When the above ranges are met, the rolling density can be increased, thereby achieving a high energy density.
[0111] The first positive electrode active material and the second positive electrode active material can be contained in a weight ratio of 80:20 to 40:60, 75:25 to 45:55, 70:30 to 50:50, or 65:45 to 55:45. When the above weight ratios are met, the effect of improving high-temperature lifetime characteristics and resistivity characteristics while increasing energy density can be maximized.
[0112] Meanwhile, when silicon-based active materials are used as the negative electrode active materials, these materials function within the discharge terminal voltage range. At this point, when the discharge terminal resistance of the positive electrode is low, lithium deposition occurs on the negative electrode surface due to the resistance difference between the positive and negative electrodes. Therefore, to reduce the discharge terminal resistance difference between the positive and negative electrodes, the discharge terminal resistance of the positive electrode can be increased. However, if the interface resistance of the positive electrode increases throughout the entire range, the cell resistance will increase.
[0113] Therefore, the positive electrode of the present invention solves the above-mentioned problems by maintaining the interface resistance of the positive electrode with a SOC of 50% in a coin half-cell manufactured using the positive electrode and increasing the interface resistance of the positive electrode with a SOC of 10% measured in a coin half-cell manufactured using the positive electrode.
[0114] In a coin cell manufactured using a positive electrode, the interface resistance of the positive electrode with a SOC of 50% is between 6.5 Ω and 8.5 Ω. Specifically, in a coin cell manufactured using a positive electrode, the interface resistance of the positive electrode with a SOC of 50% can be 6.5 Ω or higher, 6.7 Ω or higher, 6.9 Ω or higher, 7.0 Ω or higher, or 7.2 Ω or higher, and can be below 8.5 Ω, 8.3 Ω or lower, 8.1 Ω or lower, 8.0 Ω or lower, 7.8 Ω or lower, 7.6 Ω or lower, or 7.4 Ω or lower. For example, in a coin cell manufactured using a positive electrode, the interface resistance of the positive electrode with a SOC of 50% can be between 6.5 Ω and 8.5 Ω, 6.7 Ω and 8.0 Ω, or 6.9 Ω and 7.4 Ω. When the above range is met, the interface resistance of the positive electrode can be maintained at 50% SOC without increasing, so that the overall resistance of the cell does not increase, thereby avoiding the problem of increased initial resistance during charging and discharging, thus improving the life characteristics of the cell.
[0115] Furthermore, in coin-type half-cells manufactured using the positive electrode, the interface resistance of the positive electrode with a SOC of 10% is between 15 Ω and 19 Ω. Specifically, in coin-type half-cells manufactured using the positive electrode, the interface resistance of the positive electrode with a SOC of 10% can be 15 Ω or higher, 15.2 Ω or higher, 15.4 Ω or higher, 15.6 Ω or higher, 15.8 Ω or higher, 16 Ω or higher, 16.2 Ω or higher, 16.4 Ω or higher, 16.6 Ω or higher, 16.8 Ω or higher, 17 Ω or higher, 17.2 Ω or higher, or 17.4 Ω or higher, and can be less than 19 Ω, less than 18.8 Ω, less than 18.6 Ω, less than 18.4 Ω, less than 18.2 Ω, less than 18 Ω, less than 17.8 Ω, or less than 17.6 Ω. For example, in a coin-sized battery cell using a positive electrode, the interface resistance of the positive electrode with a SOC of 10% can be 15 Ω to 19 Ω, 15.2 Ω to 18 Ω, 16 Ω to 17.8 Ω, or 17 Ω to 17.6 Ω. When these ranges are met, the resistance difference between the positive and negative electrodes at the end of discharge can be reduced, thereby suppressing lithium-ion deposition on the negative electrode surface, inhibiting negative electrode degradation, solving the problem of battery cycle characteristic deterioration, preventing the increase in initial resistance during charging and discharging, and thus improving battery life characteristics.
[0116] At this point, in the coin half-cell, the interfacial resistance of the positive electrode with a SOC of 50% or 10% can be controlled by the composition of the first positive electrode active material and the second positive electrode active material, the cobalt content of the first coating contained in the first positive electrode active material and the second coating contained in the second positive electrode active material, and the rinsing conditions during the manufacture of the first positive electrode active material and the second positive electrode active material.
[0117] The IRR value of the positive electrode of the present invention, as defined by Equation 1 below, is 96 to 166. Specifically, the IRR value defined by Equation 1 can be 96 or more, 98 or more, 100 or more, 102 or more, 104 or more, 106 or more, 108 or more, 110 or more, 112 or more, 116 or more, 118 or more, 120 or more, 122 or more, 124 or more, 126 or more, and can be 166 or less, 164 or less, 162 or less, 160 or less, 158 or less, 156 or less, 154 or less, 152 or less, 150 or less, 148 or less, 146 or less, 144 or less, 142 or less, 140 or less, 138 or less, 136 or less, 134 or less, 132 or less, 130 or less, or 128 or less. For example, the IRR value defined by Equation 1 can be 96 to 166, 100 to 140, 104 to 130, 120 to 130, or 124 to 128. When the above IRR range is met, the interface resistance of the positive electrode can be controlled within a certain range, so that the resistance of the positive electrode will not increase throughout the region, and the discharge end resistance difference between the positive and negative electrodes is reduced. Therefore, the high-temperature life characteristics of the lithium secondary battery can be excellent.
[0118] (Equation 1)
[0119] IRR = R CT50 ×R CT10
[0120] In equation 1, R CT50 R is a dimensionless interfacial resistance (in Ω) of the positive electrode in a coin cell with a state of charge (SOC) of 50%, measured using the positive electrode. CT10 It is a dimensionless number of the interfacial resistance (in Ω) of the positive electrode in a coin cell with a state of charge (SOC) of 10% measured using the positive electrode.
[0121] In R CT50 The interface resistance of the positive electrode in a coin half-cell manufactured using the positive electrode, with a SOC of 50%, can be the same as described above.
[0122] In R CT10 The interface resistance of the positive electrode in a coin half-cell manufactured using the positive electrode with a SOC of 10% can be the same as described above.
[0123] Meanwhile, the positive electrode active material layer may optionally further include at least one of a positive electrode conductive material and a positive electrode binder.
[0124] The positive electrode conductive material used to impart conductivity to the electrode can be any material that is conductive and does not cause chemical changes in the battery to be constructed, without any particular limitations. Specific examples include: graphite, such as natural or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermally cracked carbon black, carbon fibers, and carbon nanotubes; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, which can be used alone or in mixtures of two or more thereof. Based on the total weight of the positive electrode active material layer, the content of the positive electrode conductive material can typically be 1 to 30% by weight, 1 to 20% by weight, or 1 to 10% by weight.
[0125] The positive electrode binder is used to improve adhesion between positive electrode particles and between the positive electrode and the positive electrode current collector. Specific examples include fluoropolymer binders, including: polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE); rubber binders, including styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber, and styrene-isoprene rubber; cellulose binders, including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, and regenerated cellulose; polyol binders, including polyvinyl alcohol; polyolefin binders, including polyethylene and polypropylene; polyimide binders; polyester binders; and silane binders, and one or more of these may be used alone. Based on the total weight of the positive electrode active material layer, the content of the positive electrode binder may be 1 to 30% by weight, 1 to 20% by weight, or 1 to 10% by weight.
[0126] The positive electrode can be manufactured by coating a positive electrode slurry onto one or both sides of an elongated positive electrode current collector, removing the solvent from the positive electrode slurry through a drying process, and then rolling it. Meanwhile, a positive electrode containing an uncoated portion can be manufactured by not coating a specific area of the positive electrode current collector, such as one end of the positive electrode current collector, with the positive electrode slurry not applied during the coating process.
[0127] Alternatively, the positive electrode slurry can be prepared by dispersing the first and second positive electrode active materials of the present invention in a solvent such as dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone or water.
[0128] Lithium secondary batteries
[0129] Next, the lithium secondary battery of the present invention will be described.
[0130] The present invention provides a lithium secondary battery comprising: an electrode assembly including the above-mentioned positive and negative electrodes; an electrolyte; and a battery casing accommodating the electrode assembly and the electrolyte, wherein the negative electrode comprises a silicon-based negative electrode active material.
[0131] Each component of the lithium secondary battery of the present invention will be described in more detail below.
[0132] (1) Electrode assembly
[0133] The electrode assembly of the present invention includes a positive electrode and a negative electrode. Specifically, the electrode assembly may include a positive electrode, a negative electrode, and a separator.
[0134] Specifically, the electrode assembly can be formed by stacking a positive electrode, a separator, and a negative electrode in sequence, and the positive and negative electrodes can be insulated from each other by the separator.
[0135] Electrode assemblies may be of types including, but not limited to, stacked, coiled, and stacked & folded.
[0136] Each component of the electrode assembly of the present invention is described in detail below.
[0137] 1) Positive electrode
[0138] Since the positive electrode is the same as described above, a detailed description is omitted.
[0139] 2) Negative electrode
[0140] The negative electrode comprises a silicon-based negative electrode active material. For example, the negative electrode may include: a negative electrode current collector; and a negative electrode active material layer, and the negative electrode active material layer may comprise a silicon-based negative electrode active material.
[0141] There are no particular restrictions on the negative electrode current collector, as long as it has high conductivity and does not cause chemical changes in the battery. Examples include copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, or silver, and aluminum-cadmium alloys. The negative electrode current collector can typically have a thickness of about 3 μm to 500 μm.
[0142] In addition, similar to positive electrode current collectors, negative electrode current collectors can have fine irregularities formed on their surface to enhance the bonding strength of the negative electrode active material. For example, negative electrode current collectors can be used in various forms, such as membranes, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics.
[0143] The negative electrode active material layer can be located on the negative electrode current collector, or on one or both sides of the negative electrode current collector. The negative electrode active material layer can be a single layer or a multilayer structure with two or more layers.
[0144] Silicon-based anode active materials can be silicon (Si)-containing particles.
[0145] Silicon-based anode active materials can be SiO x (0≤x≤2), Si / C composites or combinations thereof. x (0≤x≤2) can be in the form of including both Si and SiO2. In other words, x corresponds to SiO2. x The ratio of O to Si contained in (0≤x≤2). According to one embodiment, the silicon-based anode active material can be SiO₂. x (0≤x≤2), the optimal choice is SiO.
[0146] When the negative electrode contains silicon-based negative electrode active material, it has the advantage of significantly higher charge / discharge capacity compared to conventional carbon-based negative electrode active materials. However, silicon-based negative electrode active materials suffer from large irreversible capacity, which reduces the battery's lifespan. However, as described above, the lithium secondary battery of the present invention solves this problem by including a single-particle positive electrode active material in the positive electrode and controlling the interface resistance of the positive electrode within a specific range.
[0147] The content of silicon-based anode active material in the anode active material layer can be from 1% to 30% by weight, from 1% to 25% by weight, or from 2% to 20% by weight. When the above ranges are met, sufficient capacity characteristics can be achieved.
[0148] The negative electrode active material layer may further include carbon-based negative electrode active material as the negative electrode active material.
[0149] The carbon-based anode active material can be selected from at least one of the following: graphite, such as natural graphite and artificial graphite; and carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, and carbon nanotubes. When a carbon-based anode active material is included, the degradation of lifetime characteristics caused by volume changes in silicon-based anode active materials can be suppressed during charging and discharging.
[0150] When further comprising carbon-based anode active material, the silicon-based anode active material and the carbon-based anode active material can be contained in a weight ratio of 1:99 to 30:70, 1.5:98.5 to 20:80, 2:98 to 15:85, or 2.5:97.5 to 10:90. Within the above ranges, excellent capacity characteristics and excellent lifetime characteristics can be achieved.
[0151] The content of carbon-based anode active material in the anode active material layer can be 70% to 99% by weight, 75% to 99% by weight, or 80% to 98% by weight. When the above ranges are met, the battery life characteristics can be improved while achieving sufficient capacity characteristics.
[0152] The negative electrode active material layer may optionally further include a negative electrode conductive agent and a negative electrode binder.
[0153] Negative electrode conductive materials are used to impart conductivity to the electrode, and there are no particular limitations on their use, as long as they are conductive and do not cause chemical changes in the battery to be constructed. Specific examples include: graphite, such as natural or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermally cracked carbon black, carbon fibers, and carbon nanotubes; metal powders or fibers such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, which can be used alone or in mixtures of two or more thereof. Based on the total weight of the negative electrode active material layer, the content of the negative electrode conductive material is typically 1 to 30% by weight, 1 to 20% by weight, or 1 to 10% by weight.
[0154] Negative electrode binders are used to improve the adhesion between negative electrode active material particles and the adhesion strength between the negative electrode active material and the negative electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, which can be used alone or in mixtures of two or more thereof. Based on the total weight of the negative electrode active material layer, the content of the negative electrode conductive material is typically 1 to 30% by weight, 1 to 20% by weight, or 1 to 10% by weight.
[0155] 3) Diaphragm
[0156] Next, the separator separates the negative and positive electrodes from each other while providing a migration path for lithium ions. There are no particular limitations, as long as it is commonly used as a separator in lithium-ion secondary batteries. The separator can be positioned between the positive and negative electrodes.
[0157] Specifically, the diaphragm can be a porous polymer membrane, such as a porous polymer membrane made of polyolefin polymers (e.g., ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer), or a laminated structure of two or more layers thereof. Alternatively, conventional porous nonwoven fabrics can be used, such as nonwoven fabrics made of high-melting-point glass fibers or polyethylene terephthalate fibers. Additionally, coated diaphragms containing ceramic components or polymer materials can be used to ensure heat resistance or mechanical strength.
[0158] (2) Electrolytes
[0159] The electrolyte of this invention comprises lithium salt and organic solvent.
[0160] Lithium salts can be used without any particular restrictions, as long as they are compounds capable of providing lithium ions for use in lithium-ion secondary batteries. Specific lithium salts can be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt can be in the range of 0.1 M to 5.0 M or 0.1 M to 3.0 M. When the concentration of the lithium salt falls within the above range, the electrolyte has suitable conductivity and viscosity, thus achieving excellent electrolyte performance, and lithium ions can migrate efficiently.
[0161] Organic solvents may include at least one of cyclic carbonate organic solvents, linear carbonate organic solvents, linear ester organic solvents, and cyclic ester organic solvents.
[0162] Cyclic carbonate organic solvents are high-viscosity organic solvents and may include at least one selected from the group consisting of, for example, ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentene carbonate, 2,3-pentene carbonate, and vinylene carbonate.
[0163] In addition, linear carbonate organic solvents are organic solvents with low viscosity and low dielectric constant, and may include at least one selected from, for example, dimethyl carbonate (DMC), diethyl carbonate (DEC) and dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate and ethyl propyl carbonate, specifically including ethyl methyl carbonate (EMC).
[0164] The straight-chain ester organic solvent can be at least one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate.
[0165] Cyclic ester organic solvents may be at least one selected from the group consisting of γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone.
[0166] Preferably, the electrolyte of the present invention may include ethylene carbonate and dimethyl carbonate as organic solvents.
[0167] In addition to the electrolyte components mentioned above, the electrolyte may further include other additives for purposes such as improving battery life characteristics, suppressing battery capacity reduction, and increasing battery discharge capacity.
[0168] Other additives may include at least one selected from, for example, cyclic carbonates, halogenated carbonates, sulfonyl lactones, sulfate / esters, borates / esters, nitriles, benzenes, amines, silanes, and lithium salts that are different from the lithium salts contained in the electrolyte.
[0169] Specifically, other additives are selected from vinylene carbonate (VC), vinyl ethylene carbonate, fluoroethylene carbonate (FEC), 1,3-propane sulpholactone (PS), 1,4-butane sulpholactone, vinyl sulpholactone, 1,3-propene sulpholactone (PRS), 1,4-butene sulpholactone, 1-methyl-1,3-propene sulpholactone, ethylene sulfate (Esa), trimethylene sulfate (TMS), methyl trimethylene sulfate (MTMS), tetraphenylborate, lithium oxaloyl difluoroborate, succinate, adiponitrile, acetonitrile, propionitrile, butyronitrile, valerate, octanoic acid, heptanonitrile, cyclopentanoic acid, cyclohexanoic acid, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, 4-fluorophenylacetonitrile, fluorobenzene, triethanolamine, ethylenediamine, tetravinylsilane, and LiN(SO2F)2. One or more of the following groups: (lithium bis(fluorosulfonyl)imide, LiFSI), LiN(SO2CF3)2 (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI), LiPO2F2, LiODFB, LiBOB (lithium bis(oxalatoborate) (LiB(C2O4)2) and LiBF4).
[0170] Based on the total weight of the electrolyte, the content of other additives can be from 0.01% to 20% by weight, or from 0.05% to 5.0% by weight. When the above ranges are met, high-temperature life characteristics and low-temperature output characteristics can be improved, and side reactions in the electrolyte can be prevented.
[0171] (3) Battery casing
[0172] Battery housings are used to house electrode assemblies and electrolytes, and examples include various battery housings known in the art, such as cylindrical battery housings, prismatic battery housings, and pouch battery housings.
[0173] The lithium secondary battery of the present invention can be used in portable devices (e.g., mobile phones, laptops, and digital cameras) and electric vehicles (e.g., hybrid electric vehicles (HEVs)).
[0174] In addition, battery modules or battery packs, including lithium secondary batteries as unit cells, can be used as power sources for one or more of the following medium and large-sized devices: power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs) and plug-in hybrid electric vehicles (PHEVs); and power storage systems.
[0175] The lithium secondary battery of the present invention can be used not only as a battery cell for powering small devices, but also as a unit cell in medium and large battery modules containing multiple battery cells.
[0176] Examples of medium to large-sized equipment include, but are not limited to, electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and energy storage systems.
[0177] Method for manufacturing positive electrode
[0178] Next, refer to Figure 1 This describes a method for manufacturing the positive electrode of the present invention.
[0179] The method for manufacturing the positive electrode of the present invention includes: (S1) mixing a first positive electrode active material in distilled water for a first rinse, followed by drying; (S2) mixing a second positive electrode active material in distilled water for a second rinse, followed by drying; and (S3) forming a positive electrode active material layer comprising the first positive electrode active material and the second positive electrode active material, wherein the first rinse is performed at a higher temperature than the second rinse, and the average particle size D of the first positive electrode active material is... 50 The average particle size D of the second positive electrode active material is greater than that of the second positive electrode active material. 50 The first positive electrode active material and the second positive electrode active material comprise single-particle particles, and the interface resistance of the positive electrode with a SOC of 50% measured in a coin half-cell manufactured using the positive electrode is 6.5 Ω to 8.5 Ω, and the interface resistance of the positive electrode with a SOC of 10% measured in a coin half-cell manufactured using the positive electrode is 15 Ω to 19 Ω.
[0180] In the following, each step of the method for manufacturing the positive electrode of the present invention will be described in detail with reference to the accompanying drawings.
[0181] (1) Step S1: First positive electrode active material rinsing step
[0182] First, the first positive electrode active material is mixed in distilled water for a first rinse, and then dried (step S1).
[0183] The first positive electrode active material includes single-particle type particles.
[0184] Since the first positive electrode active material is the same as described above, its detailed description is omitted.
[0185] Step S1 is used to control the interface resistance of the positive electrode within a specific range by making the rinsing intensity of the first positive electrode active material higher than the rinsing intensity of the second positive electrode active material in step S2 below.
[0186] Specifically, the first rinse is performed at a higher temperature than the second rinse.
[0187] The first rinse is performed at 20°C to 40°C, 25°C to 35°C, or 27°C to 38°C. When the first rinse is performed at the above temperatures, the interface resistance of the positive electrode can be controlled within the desired range.
[0188] Alternatively, the first rinse can be performed by mixing the first positive electrode active material with an amount of 50% to 70% by weight, 55% to 65% by weight, or 57% to 63% by weight based on the total weight of distilled water. In this case, the amount of residual lithium on the surface of the positive electrode active material can be reduced, thereby preventing degradation of high-temperature durability.
[0189] Drying can be carried out at 60°C to 200°C, 70°C to 180°C, or 80°C to 160°C.
[0190] (2) Step S2: Rinsing of the second positive electrode active material
[0191] First, the second positive electrode active material is mixed in distilled water for a second rinse, and then dried (step S2).
[0192] The second positive electrode active material comprises single-particle type particles. When the second positive electrode active material comprises single-particle type particles, the larger particle size results in a longer lithium diffusion distance, which increases diffusion resistance and may lead to lower positive electrode efficiency. This balances the efficiency with the negative electrode when using silicon-based negative electrode active materials. Therefore, the problem of lithium-ion loss due to irreversible capacity when using conventional silicon-based negative electrode active materials can be solved, and lithium deposition on the negative electrode surface can be prevented or suppressed, thus improving the lifespan characteristics of lithium secondary batteries using the positive electrode of this invention. Furthermore, when using a second positive electrode active material with single-particle type particles, unlike when using conventional sacrificial positive electrode materials, the formation of lithium byproducts caused by sacrificial positive electrode materials during charging and discharging can be prevented or suppressed, resulting in excellent high-temperature storage characteristics and high-temperature lifespan characteristics.
[0193] The average particle size D of the first positive electrode active material 50 The average particle size D of the second positive electrode active material is greater than that of the second positive electrode active material. 50 .
[0194] Since the second positive electrode active material is the same as that described above, its detailed description is omitted.
[0195] Step S2 is performed by reducing the rinsing intensity of the second positive electrode active material, which has a smaller particle size and a larger specific surface area than the first positive electrode active material, thereby preventing or suppressing the degradation of the high-temperature durability of the second positive electrode active material and controlling the interface resistance of the positive electrode within a specific range.
[0196] According to one embodiment, the second flush can be performed at 3°C to 18°C, 5°C to 15°C, or 7°C to 13°C. When the second flush is performed within the above ranges, the interface resistance of the positive electrode can be controlled within the desired range, while preventing the degradation of high-temperature durability.
[0197] The second rinsing can be performed by mixing the second positive electrode active material with an amount of 65% to 85%, 70% to 80%, or 72% to 78% of the total weight of distilled water. In this case, the amount of residual lithium on the surface of the positive electrode active material can be reduced, thereby preventing degradation of high-temperature durability.
[0198] Drying can be carried out at 60°C to 200°C, 70°C to 180°C, or 80°C to 160°C.
[0199] (3) Step S3: Formation of positive electrode active material layer
[0200] Next, the step of forming a positive electrode active material layer including a first positive electrode active material and a second positive electrode active material is carried out (step S3).
[0201] First, the first positive electrode active material, the second positive electrode active material, and the solvent can be mixed to prepare the positive electrode slurry.
[0202] Since the first and second positive electrode active materials are the same as described above, their detailed descriptions are omitted.
[0203] The positive electrode slurry may optionally further include a positive electrode binder and / or a positive electrode conductive material.
[0204] Since the positive electrode adhesive and positive electrode conductive material are the same as those described above, their detailed descriptions are omitted.
[0205] Meanwhile, the solvent used in the positive electrode slurry can be an aqueous solvent, an organic solvent, or a combination thereof.
[0206] The aqueous solvent may include, for example, water, and the organic solvent may include one or more selected from the group consisting of N-methylpyrrolidone (NMP), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), dihydro-L-glucanone (Cyrene), γ-valerolactone, dimethyl isosorbide (DMI), and methyl-5-(dimethylamino)-2-methyl-5-oxovalerate, or according to one embodiment, may include N-methylpyrrolidone.
[0207] Next, the positive electrode slurry can be coated onto the positive electrode current collector and dried to form a positive electrode active material layer. Specifically, the positive electrode can be manufactured by coating the positive electrode slurry onto one or both sides of the positive electrode current collector, then drying and rolling to form a positive electrode active material layer.
[0208] Since the positive electrode current collector is the same as described above, its detailed description is omitted.
[0209] Coating can be performed continuously or discontinuously using a variety of coating methods known in the art, such as slot coating, sliding coating, and curtain coating.
[0210] Drying can be carried out at 40°C to 180°C, 60°C to 160°C, or 70°C to 150°C.
[0211] Roll forming can be performed according to a rolling method that involves adjusting the gap between the upper and lower rollers to match the thickness of the positive electrode, but is not limited to this method.
[0212] Meanwhile, in a coin-type half-cell battery using a positive electrode, the interface resistance of the positive electrode with a SOC of 50% is 6.5 Ω to 8.5 Ω. Specifically, in a coin-type half-cell battery using a positive electrode, the interface resistance of the positive electrode with a SOC of 50% can be 6.5 Ω or higher, 6.7 Ω or higher, 6.9 Ω or higher, 7.0 Ω or higher, or 7.2 Ω or higher, and can be below 8.5 Ω, 8.3 Ω or lower, 8.1 Ω or lower, 8.0 Ω or lower, 7.8 Ω or lower, 7.6 Ω or lower, or 7.4 Ω or lower. For example, in a coin-type half-cell battery using a positive electrode, the interface resistance of the positive electrode with a SOC of 50% can be 6.5 Ω to 8.5 Ω, 6.7 Ω to 8.0 Ω, or 6.9 Ω to 7.4 Ω. When the above range is met, the interface resistance of the positive electrode can be maintained at 50% SOC without increasing, so that the overall resistance of the cell does not increase, thereby avoiding the problem of increased initial resistance during charging and discharging, thus improving the life characteristics of the cell.
[0213] Furthermore, in coin-type half-cells manufactured using the positive electrode, the interface resistance of the positive electrode with a SOC of 10% is between 15 Ω and 19 Ω. Specifically, in coin-type half-cells manufactured using the positive electrode, the interface resistance of the positive electrode with a SOC of 10% can be 15 Ω or higher, 15.2 Ω or higher, 15.4 Ω or higher, 15.6 Ω or higher, 15.8 Ω or higher, 16 Ω or higher, 16.2 Ω or higher, 16.4 Ω or higher, 16.6 Ω or higher, 16.8 Ω or higher, 17 Ω or higher, 17.2 Ω or higher, or 17.4 Ω or higher, and can be less than 19 Ω, less than 18.8 Ω, less than 18.6 Ω, less than 18.4 Ω, less than 18.2 Ω, less than 18 Ω, less than 17.8 Ω, or less than 17.6 Ω. For example, in a coin-sized battery cell using a positive electrode, the interface resistance of the positive electrode with a SOC of 10% can be 15 Ω to 19 Ω, 15.2 Ω to 18 Ω, 16 Ω to 17.8 Ω, or 17 Ω to 17.6 Ω. When these ranges are met, the resistance difference between the positive and negative electrodes at the end of discharge can be reduced, thereby suppressing lithium-ion deposition on the negative electrode surface, inhibiting negative electrode degradation, solving the problem of battery cycle characteristic deterioration, preventing or suppressing the increase in initial resistance during charging and discharging, and thus improving battery life characteristics.
[0214] Since the positive electrode is the same as described above, its detailed description is omitted.
[0215] Hereinafter, embodiments of the invention are described in detail to enable those skilled in the art to readily practice the invention. However, the invention can be implemented in many different forms and is not limited to the embodiments described herein.
[0216] Example 1
[0217] <Preparation of the First Positive Electrode Active Material>
[0218] A transition metal aqueous solution was prepared by mixing NiSO4, CoSO4 and MnSO4 in distilled water at a nickel:cobalt:manganese molar ratio of 83:7:10.
[0219] Subsequently, deionized water was introduced into the reactor, which was then purged with nitrogen to remove dissolved oxygen and establish a non-oxidizing atmosphere within the reactor. Following this, a co-precipitation reaction was carried out while adding NaOH to prepare an average particle size D. 50 It is 8.6 μm and made of Ni 0.83 Co 0.07 Mn 0.1 (OH)2 represents the precursor.
[0220] The precursor and LiOH were mixed in a ratio of 1:1.05, Al was added as a dopant element, and the mixture was calcined at 910 °C for 16 hours to prepare Li[Ni] 0.81 Co 0.07 Mn 0.10 Al 0.02 O2 represents the first lithium transition metal oxide.
[0221] Then, the first lithium transition metal oxide was washed with distilled water at 30°C until the solid content reached 60% by weight, dried, and then mixed with Co(OH)₂. It was then heat-treated at 750°C for 5 hours to prepare the Co-coated first positive electrode active material. It was confirmed that the first positive electrode active material contained 3 mol% Co and had an average particle size D. 50 It has a size of 8.6 μm and is a single-particle type.
[0222] <Preparation of the Second Positive Electrode Active Material>
[0223] A transition metal aqueous solution was prepared by mixing NiSO4, CoSO4 and MnSO4 in distilled water at a nickel:cobalt:manganese molar ratio of 83:7:10.
[0224] Subsequently, deionized water was introduced into the reactor, which was then purged with nitrogen to remove dissolved oxygen and establish a non-oxidizing atmosphere within the reactor. Following this, a co-precipitation reaction was carried out while adding NaOH to prepare an average particle size D. 50 It is 3.1 μm and made of Ni 0.83 Co 0.07 Mn 0.1 (OH)2 represents the precursor.
[0225] The precursor and LiOH were mixed in a ratio of 1:1.05, Al was added as a dopant element, and the mixture was calcined at 910 °C for 16 hours to prepare Li[Ni] 0.81 Co 0.07 Mn 0.10 Al 0.02 O2 represents the second lithium transition metal oxide.
[0226] Then, the second lithium transition metal oxide was washed with distilled water at 10°C until the solid content reached 75% by weight, dried, and then mixed with Co(OH)₂. It was then heat-treated at 750°C for 5 hours to prepare the Co-coated second positive electrode active material. It was confirmed that the second positive electrode active material contained 1 mol% Co and had an average particle size D. 50 It has a size of 3.1 μm and, like the first positive electrode active material, is a single-particle type.
[0227] <The Manufacturing of the Positive Electrode>
[0228] The first and second positive electrode active materials prepared as described above were mixed at a weight ratio of 60:40 to prepare the positive electrode material. The positive electrode material, carbon black as a conductive agent, and polyvinylidene fluoride (PVDF) as a binder were mixed in an N-methylpyrrolidone solvent at a weight ratio of 96:2:2 to prepare the positive electrode slurry. The positive electrode slurry was coated onto one side of an aluminum current collector with a thickness of 20 μm, dried at 130°C, and then rolled to produce a positive electrode with a thickness of 70 μm.
[0229] Example 2
[0230] <Preparation of the First Positive Electrode Active Material>
[0231] A transition metal aqueous solution was prepared by mixing NiSO4, CoSO4 and MnSO4 in distilled water at a nickel:cobalt:manganese molar ratio of 83:7:10.
[0232] Subsequently, deionized water was introduced into the reactor, which was then purged with nitrogen to remove dissolved oxygen and establish a non-oxidizing atmosphere within the reactor. Following this, a co-precipitation reaction was carried out while adding NaOH to prepare an average particle size D. 50 It is 8.4 μm and made of Ni 0.83 Co 0.07 Mn 0.1 (OH)2 represents the precursor.
[0233] The precursor and LiOH were mixed in a ratio of 1:1.05, Al was added as a dopant element, and the mixture was calcined at 910 °C for 16 hours to prepare Li[Ni] 0.81 Co 0.07 Mn 0.10 Al 0.02 O2 represents the first lithium transition metal oxide.
[0234] Then, the first lithium transition metal oxide was washed with distilled water at 25°C until the solid content reached 60% by weight, dried, and then mixed with Co(OH)₂. It was then heat-treated at 750°C for 5 hours to prepare the Co-coated first positive electrode active material. It was confirmed that the first positive electrode active material contained 3 mol% Co and had an average particle size D. 50 It has a size of 8.4 μm and is a single-particle type.
[0235] <Preparation of the Second Positive Electrode Active Material>
[0236] A transition metal aqueous solution was prepared by mixing NiSO4, CoSO4 and MnSO4 in distilled water at a nickel:cobalt:manganese molar ratio of 83:7:10.
[0237] Subsequently, deionized water was introduced into the reactor, which was then purged with nitrogen to remove dissolved oxygen and establish a non-oxidizing atmosphere within the reactor. Following this, a co-precipitation reaction was carried out while adding NaOH to prepare an average particle size D. 50 It is 3.3 μm and made of Ni 0.83 Co 0.07 Mn 0.1 (OH)2 represents the precursor.
[0238] The precursor and LiOH were mixed in a ratio of 1:1.05, Al was added as a dopant element, and the mixture was calcined at 910 °C for 16 hours to prepare Li[Ni] 0.81 Co 0.07 Mn 0.10 Al 0.02 O2 represents the second lithium transition metal oxide.
[0239] Then, the second lithium transition metal oxide was washed with distilled water at 15°C until the solid content reached 75% by weight, dried, and then mixed with Co(OH)₂. It was then heat-treated at 750°C for 5 hours to prepare the Co-coated second positive electrode active material. It was confirmed that the second positive electrode active material contained 1 mol% Co and had an average particle size D. 50 It has a size of 3.3 μm and is a single-particle type.
[0240] <The Manufacturing of the Positive Electrode>
[0241] The positive electrode was manufactured in the same manner as in Example 1, except that the first positive electrode active material and the second positive electrode active material prepared above were used.
[0242] Example 3
[0243] <Preparation of the First Positive Electrode Active Material>
[0244] A transition metal aqueous solution was prepared by mixing NiSO4, CoSO4 and MnSO4 in distilled water at a nickel:cobalt:manganese molar ratio of 83:7:10.
[0245] Subsequently, deionized water was introduced into the reactor, which was then purged with nitrogen to remove dissolved oxygen and establish a non-oxidizing atmosphere within the reactor. Following this, a co-precipitation reaction was carried out while adding NaOH to prepare an average particle size D. 50 It is 8.1 μm and made of Ni 0.83 Co 0.07 Mn 0.1 (OH)2 represents the precursor.
[0246] The precursor and LiOH were mixed in a ratio of 1:1.05, Al was added as a dopant element, and the mixture was calcined at 910 °C for 16 hours to prepare Li[Ni] 0.81 Co 0.07 Mn 0.10 Al 0.02 O2 represents the first lithium transition metal oxide.
[0247] Then, the first lithium transition metal oxide was washed with distilled water at 30°C until the solid content reached 60% by weight, dried, and then mixed with Co(OH)₂. The mixture was then heat-treated at 750°C for 5 hours to prepare the Co-coated first positive electrode active material. It was confirmed that the first positive electrode active material contained 2.5 mol% Co and had an average particle size D. 50 It has a size of 8.1 μm and is a single-particle type.
[0248] <Preparation of the Second Positive Electrode Active Material>
[0249] A transition metal aqueous solution was prepared by mixing NiSO4, CoSO4 and MnSO4 in distilled water at a nickel:cobalt:manganese molar ratio of 83:7:10.
[0250] Subsequently, deionized water was introduced into the reactor, which was then purged with nitrogen to remove dissolved oxygen and establish a non-oxidizing atmosphere within the reactor. Following this, a co-precipitation reaction was carried out while adding NaOH to prepare an average particle size D. 50 It is 3.5 μm and made of Ni 0.83 Co 0.07 Mn 0.1 (OH)2 represents the precursor.
[0251] The precursor and LiOH were mixed in a ratio of 1:1.05, Al was added as a dopant element, and the mixture was calcined at 910 °C for 16 hours to prepare Li[Ni] 0.81 Co 0.07 Mn 0.10 Al 0.02 O2 represents the second lithium transition metal oxide.
[0252] Then, the second lithium transition metal oxide was washed with distilled water at 10°C until the solid content reached 75% by weight, dried, and then mixed with Co(OH)₂. The mixture was then heat-treated at 750°C for 5 hours to prepare the Co-coated second positive electrode active material. It was confirmed that the second positive electrode active material contained 1.5 mol% Co and had an average particle size D. 50 It has a size of 3.5 μm and is a single-particle type.
[0253] <The Manufacturing of the Positive Electrode>
[0254] The positive electrode was manufactured in the same manner as in Example 1, except that the first positive electrode active material and the second positive electrode active material prepared above were used.
[0255] Comparative Example 1
[0256] <Preparation of the First Positive Electrode Active Material>
[0257] A transition metal aqueous solution was prepared by mixing NiSO4, CoSO4 and MnSO4 in distilled water at a nickel:cobalt:manganese molar ratio of 83:7:10.
[0258] Subsequently, deionized water was introduced into the reactor, which was then purged with nitrogen to remove dissolved oxygen and establish a non-oxidizing atmosphere within the reactor. Following this, a co-precipitation reaction was carried out while adding NaOH to prepare an average particle size D. 50 It is 7.2 μm and made of Ni 0.83 Co 0.07 Mn 0.1 (OH)2 represents the precursor.
[0259] The precursor and LiOH were mixed in a ratio of 1:1.05, Al was added as a dopant element, and the mixture was calcined at 910 °C for 16 hours to prepare Li[Ni] 0.81 Co 0.07 Mn 0.10 Al 0.02 O2 represents the first lithium transition metal oxide.
[0260] Then, the first lithium transition metal oxide was washed and dried in distilled water at 10°C until the solid content reached 75% by weight, and then mixed with Co(OH)₂. It was then heat-treated at 750°C for 5 hours to prepare the Co-coated first positive electrode active material. It was confirmed that the first positive electrode active material contained 3 mol% Co and had an average particle size D. 50 It has a size of 7.2 μm and is a single-particle type.
[0261] <Preparation of the Second Positive Electrode Active Material>
[0262] A transition metal aqueous solution was prepared by mixing NiSO4, CoSO4 and MnSO4 in distilled water at a nickel:cobalt:manganese molar ratio of 83:7:10.
[0263] Subsequently, deionized water was introduced into the reactor, which was then purged with nitrogen to remove dissolved oxygen and establish a non-oxidizing atmosphere within the reactor. Following this, a co-precipitation reaction was carried out while adding NaOH to prepare an average particle size D. 50 It is 2.5 μm and made of Ni 0.83 Co0.07 Mn 0.1 (OH)2 represents the precursor.
[0264] The precursor and LiOH were mixed in a ratio of 1:1.05, Al was added as a dopant element, and the mixture was calcined at 910 °C for 16 hours to prepare Li[Ni] 0.81 Co 0.07 Mn 0.10 Al 0.02 O2 represents the second lithium transition metal oxide.
[0265] Then, the second lithium transition metal oxide was washed with distilled water at 10°C until the solid content reached 75% by weight, dried, and then mixed with Co(OH)₂. It was then heat-treated at 750°C for 5 hours to prepare the Co-coated second positive electrode active material. It was confirmed that the second positive electrode active material contained 1 mol% Co and had an average particle size D. 50 It has a size of 2.5 μm and is a single-particle type.
[0266] <The Manufacturing of the Positive Electrode>
[0267] The positive electrode was manufactured in the same manner as in Example 1, except that the first positive electrode active material and the second positive electrode active material prepared above were used.
[0268] Comparative Example 2
[0269] <Preparation of the First Positive Electrode Active Material>
[0270] A transition metal aqueous solution was prepared by mixing NiSO4, CoSO4 and MnSO4 in distilled water at a nickel:cobalt:manganese molar ratio of 83:7:10.
[0271] Subsequently, deionized water was introduced into the reactor, which was then purged with nitrogen to remove dissolved oxygen and establish a non-oxidizing atmosphere within the reactor. Following this, a co-precipitation reaction was carried out while adding NaOH to prepare an average particle size D. 50 It is 7.7 μm and made of Ni 0.83 Co 0.07 Mn 0.1 (OH)2 represents the precursor.
[0272] The precursor and LiOH were mixed in a ratio of 1:1.05, Al was added as a dopant element, and the mixture was calcined at 910 °C for 16 hours to prepare Li[Ni] 0.81 Co 0.07 Mn 0.10 Al 0.02 O2 represents the first lithium transition metal oxide.
[0273] Then, the first lithium transition metal oxide was washed with distilled water at 30°C until the solid content reached 60% by weight, dried, and then mixed with Co(OH)₂. It was then heat-treated at 750°C for 5 hours to prepare the Co-coated first positive electrode active material. It was confirmed that the first positive electrode active material contained 1 mol% Co and had an average particle size D. 50 It has a size of 7.7 μm and is a single-particle type.
[0274] <Preparation of the Second Positive Electrode Active Material>
[0275] A transition metal aqueous solution was prepared by mixing NiSO4, CoSO4 and MnSO4 in distilled water at a nickel:cobalt:manganese molar ratio of 83:7:10.
[0276] Subsequently, deionized water was introduced into the reactor, which was then purged with nitrogen to remove dissolved oxygen and establish a non-oxidizing atmosphere within the reactor. Following this, a co-precipitation reaction was carried out while adding NaOH to prepare an average particle size D. 50 It is 2.9 μm and is made of Ni 0.83 Co 0.07 Mn 0.1 (OH)2 represents the precursor.
[0277] The precursor and LiOH were mixed in a ratio of 1:1.05, Al was added as a dopant element, and the mixture was calcined at 910 °C for 16 hours to prepare Li[Ni] 0.81 Co 0.07 Mn 0.10 Al 0.02 O2 represents the second lithium transition metal oxide.
[0278] Then, the second lithium transition metal oxide was washed with distilled water at 10°C until the solid content reached 70% by weight, dried, and then mixed with Co(OH)₂. It was then heat-treated at 750°C for 5 hours to prepare the Co-coated second positive electrode active material. It was confirmed that the second positive electrode active material contained 1 mol% Co and had an average particle size D. 50 It has a size of 2.9 μm and is a single-particle type.
[0279] <The Manufacturing of the Positive Electrode>
[0280] The positive electrode was manufactured in the same manner as in Example 1, except that the first positive electrode active material and the second positive electrode active material prepared above were used.
[0281] Comparative Example 3
[0282] <Preparation of the First Positive Electrode Active Material>
[0283] A transition metal aqueous solution was prepared by mixing NiSO4, CoSO4 and MnSO4 in distilled water at a nickel:cobalt:manganese molar ratio of 83:7:10.
[0284] Subsequently, deionized water was introduced into the reactor, which was then purged with nitrogen to remove dissolved oxygen and establish a non-oxidizing atmosphere within the reactor. Following this, a co-precipitation reaction was carried out while adding NaOH to prepare an average particle size D. 50 It is 8.5 μm and made of Ni 0.83 Co 0.07 Mn 0.1 (OH)2 represents the precursor.
[0285] The precursor and LiOH were mixed in a ratio of 1:1.05, Al was added as a dopant element, and the mixture was calcined at 910 °C for 16 hours to prepare Li[Ni] 0.81 Co 0.07 Mn 0.10 Al 0.02 O2 represents the first lithium transition metal oxide.
[0286] Then, the first lithium transition metal oxide was washed and dried in distilled water at 10°C until the solid content reached 75% by weight, and then mixed with Co(OH)₂. It was then heat-treated at 750°C for 5 hours to prepare the Co-coated first positive electrode active material. It was confirmed that the first positive electrode active material contained 3 mol% Co and had an average particle size D. 50 It has a size of 8.5 μm and is a single-particle type.
[0287] <Preparation of the Second Positive Electrode Active Material>
[0288] A transition metal aqueous solution was prepared by mixing NiSO4, CoSO4 and MnSO4 in distilled water at a nickel:cobalt:manganese molar ratio of 83:7:10.
[0289] Subsequently, deionized water was introduced into the reactor, which was then purged with nitrogen to remove dissolved oxygen and establish a non-oxidizing atmosphere within the reactor. Following this, a co-precipitation reaction was carried out while adding NaOH to prepare an average particle size D. 50 It is 3.0 μm and made of Ni 0.83 Co 0.07 Mn 0.1 (OH)2 represents the precursor.
[0290] The precursor and LiOH were mixed in a ratio of 1:1.05, Al was added as a dopant element, and the mixture was calcined at 910 °C for 16 hours to prepare Li[Ni] 0.81 Co 0.07 Mn0.10 Al 0.02 O2 represents the second lithium transition metal oxide.
[0291] Then, the second lithium transition metal oxide was washed with distilled water at 10°C until the solid content reached 70% by weight, dried, and then mixed with Co(OH)₂. It was then heat-treated at 750°C for 5 hours to prepare the Co-coated second positive electrode active material. It was confirmed that the second positive electrode active material contained 1 mol% Co and had an average particle size D. 50 It has a size of 3.0 μm and is a single-particle type.
[0292] <The Manufacturing of the Positive Electrode>
[0293] The positive electrode was manufactured in the same manner as in Example 1, except that the first positive electrode active material and the second positive electrode active material prepared above were used.
[0294] Experiment 1 - Measurement of Positive Electrode Interface Resistance and Evaluation of IRR Value
[0295] The coin-shaped battery cell is manufactured through the following process: a porous polyethylene separator is inserted between each positive electrode and lithium metal negative electrode manufactured in Examples 1 to 3 and Comparative Examples 1 to 3 to prepare an electrode assembly; the electrode assembly is placed inside a battery casing; and then an electrolyte is injected into the battery casing. The electrolyte used is 1.0 M LiPF6 dissolved in a mixed organic solvent of ethylene carbonate (EC): ethyl methyl carbonate (EMC) in a volume ratio of 3:7.
[0296] Next, for each coin cell manufactured above, the battery was subjected to two cycles, followed by charging at 0.1 C to 50% and 10% SOC. Each cycle consisted of charging at 25°C under CC / CV, 0.1 C, 4.2 V, and 0.05 C cutoff conditions, and discharging at CC, 0.1 C, and 3.0 V. The positive electrode interface resistance of each coin cell at 50% and 10% SOC was then measured using a Biologic VMP3 device (in the range of 100 kHz to 10 mHz at 25°C). The measurement results are shown in Table 1 below.
[0297] In addition, the IRR value defined by Equation 1 below was calculated using the positive electrode interface resistance of coin half-cells manufactured using the positive electrodes of Examples 1 to 3 and Comparative Examples 1 to 3 at SOC 50% and SOC 10% as measured above. The calculated IRR values are shown in Table 1 below.
[0298] (Equation 1)
[0299] IRR = R CT50 ×R CT10
[0300] In equation 1, R CT50 R is a dimensionless interfacial resistance (in Ω) of the positive electrode in a coin cell with a state of charge (SOC) of 50%, measured using the positive electrode. CT10 It is a dimensionless number of the interfacial resistance (in Ω) of the positive electrode in a coin cell with a state of charge (SOC) of 10% measured using the positive electrode.
[0301] [Table 1]
[0302]
[0303] Referring to Table 1, it can be seen that, as in Examples 1, 2, and 3, when measured in a coin half-cell manufactured using the positive electrode of the present invention, the interface resistance of the positive electrode with a SOC of 50% is 6.5 Ω to 8.5 Ω, and the interface resistance of the positive electrode with a SOC of 10% is 15 Ω to 19 Ω. Furthermore, it can be seen that the IRR value is in the range of 96 or higher and 166 or lower.
[0304] Experiment Example 2 - Initial Resistance Evaluation
[0305] A negative electrode slurry was prepared by mixing the negative electrode active material (SiO:artificial graphite in a weight ratio of 5:95), the conductive material (carbon black), the binder (SBR), and the thickener (CMC) in distilled water at a weight ratio of 95.6:1.0:2.3:1.1. The negative electrode slurry was coated onto a surface of a 12 μm thick copper current collector, dried at 130°C, and then rolled to prepare the negative electrode (slurry solids content: 50% by weight of the total weight of the negative electrode slurry).
[0306] The lithium secondary battery was manufactured by inserting a porous polyethylene separator between each positive and negative electrode manufactured in Examples 1 to 3 and Comparative Example 2 to prepare an electrode assembly, placing the electrode assembly in a battery casing, and then injecting an electrolyte therein. The electrolyte used was 1.0 M LiPF6 dissolved in a mixed organic solvent of ethylene carbonate (EC): ethyl methyl carbonate (EMC) in a volume ratio of 3:7.
[0307] Each lithium-ion secondary battery manufactured as described above was charged to 4.2 V at 0.1 C in CC / CV mode at 25°C and discharged at a constant current of 0.1 C. The discharge resistance (HPPC) was then measured at 50% and 10% SOC. The results are shown in Table 2.
[0308] [Table 2]
[0309]
[0310] Referring to Table 2 above, it can be confirmed that, compared with the lithium secondary battery manufactured using the positive electrode manufactured in Comparative Example 2, the lithium secondary battery manufactured using the positive electrode manufactured in Examples 1 to 3 has a lower discharge resistance at SOC 50% and SOC 10%.
[0311] Experimental Example 3 - Evaluation of High-Temperature Lifetime Characteristics
[0312] The lithium secondary batteries, including the negative electrode manufactured in Experimental Example 2 and the positive electrodes manufactured in Examples 1 to 3 and Comparative Examples 1 to 3, were subjected to 100 cycles using an electrochemical charge / discharger. Each cycle included charging at 45°C under CC / CV, 0.05 C and 4.2 V, 0.05 C cutoff conditions, and discharging to 3.0 V under CC, 1.0 C conditions.
[0313] (1) Capacity retention rate
[0314] The capacity retention rate is calculated using the following equation, and the results are shown in Table 3 below.
[0315] Capacity retention (%) = {(Discharge capacity after 100 cycles / Discharge capacity after 1 cycle)} x 100
[0316] (2) Rate of increase in resistance
[0317] After one charge and discharge cycle, the discharge capacity after one cycle was measured using an electrochemical charge / discharger. The SOC was adjusted to 50%, and then a 2.5 C pulse was applied for 10 seconds to calculate the initial resistance based on the difference between the voltage before and after the pulse.
[0318] After 100 charge and discharge cycles, the resistance after 100 cycles was calculated using the same method as described above, and the rate of increase in resistance was calculated using the following equation. The results are shown in Table 3 below.
[0319] Resistance increase rate (%) = (Resistance after 100 cycles - Initial resistance) / Initial resistance x 100
[0320] [Table 3]
[0321]
[0322] Referring to Table 3 above, compared with lithium secondary batteries manufactured using the positive electrodes produced in Comparative Examples 1 to 3, lithium secondary batteries manufactured using the positive electrodes produced in Examples 1 to 3 exhibit higher capacity retention at 45°C and lower resistance increase at 45°C. The results show that lithium secondary batteries manufactured using the positive electrodes produced in Examples 1 to 3 possess excellent high-temperature life characteristics. Although the technology of the present invention has been described with reference to embodiments, it will be understood by those skilled in the art or of ordinary skill in the art that various modifications and changes can be made to the various embodiments of the invention without departing from the technical scope of the various embodiments of the invention as defined in the appended claims. Therefore, the technical scope of the various embodiments of the invention is not limited to the detailed description of the invention herein, but should be determined by the scope defined in the claims.
Claims
1. A positive electrode comprising: a positive electrode active material layer including a first positive electrode active material and a second positive electrode active material having different average particle diameters from each other, wherein the average particle diameter D of the first positive electrode active material is 50 greater than the average particle diameter D of the second positive electrode active material 50 , the first positive electrode active material and the second positive electrode active material include single particle type particles, and an interfacial resistance of a positive electrode measured at an SOC of 50% in a coin half cell manufactured using the positive electrode is 6.5 Ω to 8.5 Ω, and an interfacial resistance of a positive electrode measured at an SOC of 10% in a coin half cell manufactured using the positive electrode is 15 Ω to 19 Ω.
2. The positive electrode according to claim 1, wherein the first positive electrode active material includes a first lithium transition metal oxide represented by Formula 1: (Formula 1) Li 1+a1 Ni x1 Co y1 Mn z1 Al w1 M 1 v1 O2 wherein 0 ≤ a1 ≤ 0.3, 0.82 ≤ x1 < 1.0, 0 < y1 ≤ 0.2, 0 < z1 ≤ 0.2, 0 < w1 ≤ 0.2, 0 ≤ v1 ≤ 0.1, and M 1 is at least one doping element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo.
3. The positive electrode according to claim 1, wherein the second positive electrode active material includes a second lithium transition metal oxide represented by Formula 2: (Formula 2) Li 1+a2 Ni x2 Co y2 Mn z2 Al w2 M 2 v2 O2 wherein 0 ≤ a2 ≤ 0.3, 0.82 ≤ x2 < 1.0, 0 < y2 ≤ 0.2, 0 < z2 ≤ 0.2, 0 < w2 ≤ 0.2, 0 ≤ v2 ≤ 0.1, and M 2 is at least one doping element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo.
4. The positive electrode according to claim 1, wherein The average particle size D of the first positive electrode active material 50 The thickness ranges from 6 μm to 12 μm.
5. The positive electrode according to claim 1, wherein The average particle size D of the second positive electrode active material 50 The range is from 1.5 μm to 5 μm.
6. The positive electrode according to claim 1, wherein the first positive electrode active material includes a first lithium transition metal oxide and a first coating layer containing 1.5 mol% to 5 mol% of cobalt (Co) on a surface of the first lithium transition metal oxide particle.
7. The positive electrode according to claim 1, wherein the second positive electrode active material includes a second lithium transition metal oxide and a second coating layer containing 0.2 mol% to 2.5 mol% of cobalt (Co) on a surface of the second lithium transition metal oxide particle.
8. The positive electrode according to claim 1, wherein the first positive electrode active material and the second positive electrode active material are included in a weight ratio of 80:20 to 40:
60. 9.A positive electrode comprising: a positive electrode active material layer including a first positive electrode active material and a second positive electrode active material having different average particle diameters from each other, wherein the average particle diameter D of the first positive electrode active material is 50 greater than the average particle diameter D of the second positive electrode active material 50 , the first positive electrode active material and the second positive electrode active material include single particle type particles, and an IRR value as defined by Equation 1 is 96 to 166: (Equation 1) IRR = R CT50 × R CT10 wherein R CT50 is a dimensionless number of the interfacial resistance of the positive electrode in Ω, measured in a coin half-cell manufactured using the positive electrode, with a SOC of 50%, and R CT10 is a dimensionless number of the interfacial resistance of the positive electrode in Ω, which is measured in a coin half-cell manufactured using the positive electrode, with the SOC of the positive electrode being 10%. 10.A lithium secondary battery comprising: an electrode assembly including the positive electrode of any one of claims 1 to 9, a negative electrode, and a separator; an electrolyte; and a battery case in which the electrode assembly and the electrolyte are accommodated, wherein the negative electrode contains a silicon-based negative electrode active material. the negative electrode further contains a carbon-based negative electrode active material, and 11. The lithium secondary battery according to claim 10, wherein, the silicon-based negative electrode active material and the carbon-based negative electrode active material are included in a weight ratio of 1:99 to 30:
70. 12.A method of manufacturing a positive electrode, the method comprising: (S1) first washing by mixing a first positive electrode active material in distilled water, followed by drying; (S2) second washing by mixing a second positive electrode active material in distilled water, followed by drying; and (S3) forming a positive electrode active material layer including the first positive electrode active material and the second positive electrode active material, wherein the first washing is performed at a higher temperature than the second washing, The average particle diameter D of the first positive electrode active material 50 greater than the average particle diameter D of the second positive electrode active material 50 , The first positive electrode active material and the second positive electrode active material include single-particle type particles, and The interface resistance of the positive electrode measured in a coin half cell manufactured using the positive electrode is 6.5 Ω to 8.5 Ω at an SOC of 50%, and the interface resistance of the positive electrode measured in a coin half cell manufactured using the positive electrode is 15 Ω to 19 Ω at an SOC of 10%.
13. The method of claim 12, wherein, The first washing is performed at 20°C to 40°C.
14. The method of claim 12, wherein, The second washing is performed at 3°C to 18°C.
15. The method of claim 12, wherein, The first washing is performed by mixing the first positive electrode active material at a content of 50% to 70% by weight based on the total weight of distilled water.
16. The method of claim 12, wherein, The second washing is performed by mixing the second positive electrode active material at a content of 65% to 85% by weight based on the total weight of distilled water.
17. The method of claim 12, wherein, The first positive electrode active material includes a first lithium transition metal oxide represented by Formula 1: (Formula 1) Li 1+a1 Ni x1 Co y1 Mn z1 Al w1 M 1 v1 O2 wherein 0 ≤ a1 ≤ 0.3, 0.82 ≤ x1 < 1.0, 0 < y1 < 0.18, 0 < z1 < 0.18, 0 < w1 < 0.2, 0 ≤ v1 ≤ 0.1, and M 1 is at least one dopant element selected from the group consisting of W, Mo, Cr, Zr, Ti, Mg, Ta, and Nb.
18. The method of claim 12, wherein, The second positive electrode active material includes a second lithium transition metal oxide represented by Formula 2: (Formula 2) Li 1+a2 Ni x2 Co y2 Mn z2 Al w2 M 2 v2 O2 wherein 0 ≤ a2 ≤ 0.3, 0.82 ≤ x2 < 1.0, 0 < y2 < 0.18, 0 < z2 < 0.18, 0 < w2 < 0.2, 0 ≤ v2 ≤ 0.1, and M 2 is at least one dopant element selected from the group consisting of W, Mo, Cr, Zr, Ti, Mg, Ta, and Nb.
19. The method of claim 12, wherein, The first positive electrode active material includes a first lithium transition metal oxide and a first coating layer containing cobalt (Co) on the surface of the first lithium transition metal oxide particles, and The second positive electrode active material includes a second lithium transition metal oxide and a second coating layer containing cobalt (Co) on the surface of the second lithium transition metal oxide particles, wherein the content of cobalt (Co) in the first coating layer is greater than the content of cobalt (Co) in the second coating layer.
20. The method of claim 19, wherein, The amount of cobalt (Co) in the first coating layer is 1.5 mol% to 5 mol%, and the amount of cobalt (Co) in the second coating layer is 0.2 mol% to 2.5 mol%.
Citation Information
Patent Citations
Eco Friendly Insulation Wallpaper
KR1020240151560A
Positive electrode active material for nonaqueous electrolyte secondary battery, manufacturing method of same, and nonaqueous electrolyte secondary battery using same
CN103636038A
Electronic device for protecting user and / or living space using thermal sensor and method for controlling thereof
KR1020250056564A
